2014
DOI: 10.3233/jbr-140070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilization, tiller cutting and environment on plant growth and yield of European blueberry (Vaccinium myrtillus L.) in Norwegian forest fields

Abstract: Abstract. BACKGROUND:European blueberry (E. blueberry; Vaccinium myrtillus L.) is a natural resource demanded by the processing industry with potential of domestication. Therefore an investigation of the possibilities of partial cultivation of native stands was started. OBJECTIVE: To increase knowledge of how E. blueberry react to soil types, climate, mineral nutrition, organic amendments and cutting of tillers. METHODE: Five forest fields with E.blueberry stands in Norway were examined. Besides natural develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…The findings of increased fruit production and fruit set of bilberry in our study suggest enhanced bilberry yields in areas under continuous picking. These results are not in accordance with several previous studies suggesting that biomass loss and mechanical damage due to the natural herbivory (Fernández-Calvo and Obeso 2004; Hegland et al 2005) or clipping cause reductions in bilberry fruit production and fruit set (Mathisen et al 2010;Nestby et al 2014;Pato et al 2016). A number of references support our findings of increased berry production and fruit set of bilberry after biomass loss.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The findings of increased fruit production and fruit set of bilberry in our study suggest enhanced bilberry yields in areas under continuous picking. These results are not in accordance with several previous studies suggesting that biomass loss and mechanical damage due to the natural herbivory (Fernández-Calvo and Obeso 2004; Hegland et al 2005) or clipping cause reductions in bilberry fruit production and fruit set (Mathisen et al 2010;Nestby et al 2014;Pato et al 2016). A number of references support our findings of increased berry production and fruit set of bilberry after biomass loss.…”
Section: Discussioncontrasting
confidence: 98%
“…Bilberry fruit production is associated with current annual shoot size (Tolvanen and Laine 1997;Fernández-Calvo and Obeso 2004) and is linked to the ability of bilberry to produce new growth after biomass loss. In this study bilberry lost annually less than 0.5% of its total standing biomass, which is far more than 50 times lower as compared to the 25% to 100% biomass loss applied by clipping in most of the studies on bilberry performance (Tolvanen et al 1994;Nestby et al 2014;Pato et al 2016). The recovery time after severe damage takes several years (Tolvanen et al 1994;Hautala et al 2008), during which vegetative recovery prevails and bilberry fruit production is postponed (Tolvanen et al 1993b;Nestby et al 2014).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Fertile locations are more favorable than poor locations; some studies have shown that forests of medium fertility produce the largest EB yields in the boreal zone. It was also found that N and P fertilization over four years in forest fields of EB increased shoot growth, but had generally neutral or negative effect on fruit yield depending on the NP level [14]. EB have a shallow and weakly developed root system, but the biomass of rhizomes and roots may be of a similar volume as the above ground part.…”
Section: Introductionmentioning
confidence: 94%